A Potential Probiotic for Diarrhea: Clostridium tyrobutyricum Protects Against LPS-Induced Epithelial Dysfunction via IL-22 Produced By Th17 Cells in the Ileum - Xiao, Zhiping; Liu, Lujie; Pei, Xun; Sun, Wanjing; Jin, Yuyue; Yang, Shang-Tian; Wang, Minqi (Frontiers in Immunology, 2021)
Probiotics are clinically used for diarrhea and inflammatory bowel diseases in both humans and animals. Previous studies have shown that Clostridium tyrobutyricum (Ct) protects against intestinal dysfunction, while its regulatory function in the gut needs further investigation and the related mechanisms are still not fully elucidated. This study aims to further verify the protective function of Ct and reveal its underlying mechanisms in alleviating diarrhea and intestinal inflammation. Ct inhibited LPS-induced diarrhea and intestinal inflammation in the ileum. IL-22 was identified and the protective role of Ct in the ileum presented an IL-22-dependent manner according to the transcriptomic analysis and in vivo interference mice experiments. The flow cytometric analysis of immune cells in the ileum showed that Ct enhanced the proportions of Th17 cells in response to LPS. The results of in situ hybridization further verified that Ct triggered Th17 cells to produce IL-22, which combined with IL-22RA1 expressed in the epithelial cells. Moreover, Ct was unable to enhance the levels of short-chain fatty acids (SCFAs) in the ileum, suggesting that the protective role of Ct in the ileum was independent of SCFAs. This study uncovered the role of Ct in alleviating diarrhea and inflammation with the mechanism of stimulating Th17 cells in the lamina propria to produce IL-22, highlighting its potential application as a probiotic for diarrhea and inflammation in the ileum.